Identification of a novel GNAS mutation in a case of pseudohypoparathyroidism type 1A with normocalcemia - Xiao-dan Long; Jing Xiong; Zhao-hui Mo; Chang-sheng Dong; Ping Jin (BMC, 2018)
Abstract Background Pseudohypoparathyroidism type 1A (PHP1A) is a rare genetic disease primarily characterized by resistance to parathyroid hormone along with hormonal resistance and other features of Albright hereditary osteodystrophy (AHO). It is caused by heterozygous inactivating mutations in the maternal allele of the GNAS gene, which encodes the stimulatory G-protein alpha subunit (Gsα) and regulates production of the second messenger cyclic AMP (cAMP). Herein, we report a case of of PHP1A with atypical clinical manifestations (oligomenorrhea, subclinical hypothyroidism, and normocalcemia) and explore the underlying genetic cause in this patient. Methods Blood samples were collected from the patient, her family members, and 100 healthy controls. The 13 exons and flanking splice sites of the GNAS gene were amplified by PCR and sequenced. To further assess whether the novel mutation resulted in gain or loss of function of Gsα, we examined the level of cAMP activity associated with this mutation through in vitro functional studies by introducing the target mutation into a human GNAS plasmid. Results A novel heterozygous c.715A > G (p.N239D) mutation in exon 9 of the GNAS gene was identified in the patient. This mutation was also found in her mother, who was diagnosed with pseudopseudohypoparathyroidism. An in vitro cAMP assay showed a significant decrease in PTH-induced cAMP production in cells transfected with the mutant plasmid, compared to that in the wild-type control cells (P < 0.01), which was consistent with loss of Gsa activity. Conclusion We identified a novel GNAS mutation that altered Gsα function, which furthers our understanding of the pathogenesis of this disease. Screening for GNAS mutations should be considered in suspected cases of PHP1A even if the classical signs are not present.